Does Sick Absence Increase the Risk of Unemployment? - Patrik Hesselius (Uppsala University, Department of Economics, 2003)
The paper examines whether a worker's sick absence behaviour influences the risk of becoming unemployed. Swedish panel data are used to estimate the relationship between the incidence and duration of sick leave and subsequent unemployment. The results indicate that an increase in the number of sick leaves as well as an increase in the duration of sick spells is associated with higher risk of unemployment. Women have a significantly higher risk then men of unemployment associated with sick leave spells longer than 28 days. An implication of the results is that less absence-prone workers are more likely to remain employed in a recession. This in turn may in part explain the pro-cyclical pattern of aggregate Swedish sick absence rates.
urn:nbn:se:uu:diva-4483
Keywords: C41; H55; I18; J64; 330; Sick leave; sickness insurance; health; unemployment; duration analysis; Krankheit; Fehlzeit; Arbeitslosigkeit; Krankenversicherung; Dauer